PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS WEBSITE RENDERFOREST UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV UPT SD NEGERI 064992 T.A 2023/2024 - Rumahorbo, Nathalia Hizkia; Faisal, F; Simanjuntak, Eva Betty; Halimatussakdiah, Dr.; Mustika Aulia, Sri (Universitas Negeri Medan, 2024)
This study was conducted with the aim of knowing the validity, practicality, and effectiveness of animated video media based on the renderforest website on the material of likes and dislikes in improving speaking skills in grade IV elementary school students. This research was conducted in class IV of SD Negeri 064992 which amounted to 19 students. The implementation time of this research was carried out in the even semester of T.A 2023/202. The type of research used in this study is Research and Development using the ADDIE model. The data collection techniques used are interviews, observations, questionnaires and documentation. The data analysis techniques used are qualitative data analysis and quantitative data analysis. Qualitative data analysis techniques include the results of interviews, observations, questionnaires, and documentation while quantitative data analysis techniques include media design experts, material experts, questionnaire results and speaking ability assessment rubrics. The results of research and development that have been carried out obtained a percentage of media design expert validation of 86% in the œVery Valid category, material expert validation value of 100% in the œVery Valid category, practicality test based on educator responses of 93% in the œVery Practical category, practicality test based on student responses of 90% in the œVery Practical category and effectiveness test on pretest of 60% and posttest of 89% in the œVery Effective category. Thus it can be concluded that the renderforest-based animated video media developed is valid, practical, and effective in improving the speaking skills of grade IV students.